2004
DOI: 10.1111/j.1365-2524.2004.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating choice and control for older people in long-term care

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 10 publications
(16 reference statements)
6
74
0
Order By: Relevance
“…35,36 Interviews The descriptions of the phenomenon were elicited through open-ended unstructured interviews 37 (Table 1). An interview guide based on previous studies was used, 5,6,[19][20][21][22][23][24][25][26][27][28][29][30] pre-tested in two pilot interviews, evaluated with the research group and used during the interviews. Small talk was used to establish a relaxed and confidential atmosphere.…”
Section: Samplementioning
confidence: 99%
“…35,36 Interviews The descriptions of the phenomenon were elicited through open-ended unstructured interviews 37 (Table 1). An interview guide based on previous studies was used, 5,6,[19][20][21][22][23][24][25][26][27][28][29][30] pre-tested in two pilot interviews, evaluated with the research group and used during the interviews. Small talk was used to establish a relaxed and confidential atmosphere.…”
Section: Samplementioning
confidence: 99%
“…Early research in this area was often focused on the staff: its participation in decision making (Boyle, 2004;Callaghan & Wistow, 2006;Clemens & Hayes, 1997;Dunér & Nordström, 2006;Karlsson Bucht, Rasmussen, & Sandman, 2000), its balancing between protection and empowerment (Askheim, 2003;Jakobsen & Sørlie, 2010;Stalker, 2003), and its attitudes toward, advocacy for, and relationships with residents (Cook & Brown-Wilson, 2010;Nelson, 2005;Nelson et al, 2008;Ono & Asahara, 2007;Perkins et al, 2012;Tailor, Zaturenskaya, Iwamasa, & Ferrari, 2007). Studies reporting the perspectives of older individuals are sparse, but some report that autonomy is highly valued (Ball et al, 2004;Glickman et al, 1997) and others report that it is normal to adapt to the prevailing conditions in the residential care of older people (Harnett, 2010;Roth & Eckert, 2011;Söderberg, Ståhl, & Melin Emilsson, 2012).…”
Section: Previous Researchmentioning
confidence: 99%
“…Similar to other studies, older people who could no longer cope talked about being at the end of the line (Nay 1995), and believed there was no other option other than residential care. An article which compared 214 older people living in residential care with 44 older people living at home found that older people living at home perceived they had less choice than people in residential care (Boyle 2004). Most older people in this study living at home felt they had a choice and had themselves made the decision to remain at home; however, the majority of older people in residential care stated that the doctor had made the decision.…”
Section: Discussionmentioning
confidence: 59%